Pendampingan Penerapan Pembukuan Sederhana bagi Pelaku UMKM di Desa Majir Kabupaten Purworejo - Laksmi Leilani, Diah Mulya; Budiantara, Martinus (Lembaga Dongan Dosen, 2023)
MSMEs are the backbone of the economy, creating jobs, reducing economic disparities, and supporting overall economic growth. The phenomenon that occurs is that MSME players have problems, including administrative problems related to financial recording and bookkeeping in their business. Many MSME actors have not kept bookkeeping for their businesses, including MSME actors in Majir Village, Purworejo Regency. This training aims to increase MSME players' understanding of simple bookkeeping to support the progress of their MSMEs. The service method is mentoring and training. Mentoring activities were carried out on 16 and 17 September 2023 with 2 MSME. There are three stages in this activity, namely the preparation stage, implementation of assistance activities in implementing simple bookkeeping, and evaluation. The result of this activity is that MSME players can understand the importance of implementing simple bookkeeping in their business. Currently, MSMEs already have transaction books for their business activities and have implemented simple bookkeeping in their business activities.